Maternal Different Degrees of Iodine Deficiency during Pregnant and Lactation Impair the Development of Cerebellar Pinceau in Offspring - Dong, Jing; Song, Heling; Wang, Yuan; Li, Min; Yu, Ye; Wang, Yi; Chen, Jie (Frontiers in Neuroscience, 2017)
Aims: Iodine is critical for synthesis of thyroid hormones (TH). And iodine deficiency (ID) is one of the most significant reasons of mental retardation and motor memory impairment, although the potential mechanisms are still under investigation. Presently, mild ID and marginal ID are largely ignored problems for women of child bearing age. Mild ID is a subtle form of TH deficiency, which shows low levels of free thyroxine (FT4) and relatively normal free triiodothyronine (FT3) or thyroid stimulation hormone (TSH). And marginal ID is a milder form of ID with decreased total T4 (TT4) but relatively normal FT3, FT4, and TSH. Therefore, we investigated the effects of maternal different degrees of ID on the development of pinceau in cerebellar purkinje cells (PCs) and studied the expression of pinceau related protein, which is crucial for the development and maturation of pinceau. Methods and Results: Three developmental iodine deficient rat models were created by feeding dam rats with an iodine-deficient diet and deionized water supplemented with potassiumiodide. Our study showed that different degrees of ID inhibited cerebellar pinceau synapse development and maturation on postnatal day (PN) 14 and PN21. What’s more, mild and severe ID reduced the expression of AnkG, β4-spectrin, neurofascin186 and NrCAM on PN7, PN14, and PN21. However, marginal ID rarely altered expression of these proteins in the offspring. Conclusion: These results suggested that maternal mild and severe ID impaired the development and maturation of cerebellar pinceau, which may be attributed to the decrease of AnkG, β4-spectrin, neurofascin 186 and NrCAM. And the alteration of development and maturation in cerebellar pinceau in the offspring were also observed following maternal marginal ID, which is slighter than that of mild ID.